2022
DOI: 10.1039/d2nj01146h
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the intrinsic properties of platinum–cobalt nanowires for enhanced electrocatalysis of the oxygen reduction reaction

Abstract: The ability to improve intrinsic activity of nanoalloy electrocatalysts is essential for designing highly efficient electrocatalysts by optimizing basic physical properties of the nanoalloy. This report describes that the electrocatalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The above results revealed that the addition of MnO 2 as an additive can strengthen the interaction between Pt and PC. This enhanced interaction has two effects, first, the stronger interaction improves the anchoring of PC to Pt, which reduces the agglomeration of Pt NPs. ,,, Second, the stronger interaction also increases the local electron density of Pt, thus reducing the location of the d-band center, improving the binding strength of oxygen-containing intermediates, ensuring the number of active sites. , Under the combined action of the two outcomes mentioned above, Pt/M-PC catalyst has excellent ORR stability. In addition, we also studied the effect of methanol on the catalytic performance during the test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results revealed that the addition of MnO 2 as an additive can strengthen the interaction between Pt and PC. This enhanced interaction has two effects, first, the stronger interaction improves the anchoring of PC to Pt, which reduces the agglomeration of Pt NPs. ,,, Second, the stronger interaction also increases the local electron density of Pt, thus reducing the location of the d-band center, improving the binding strength of oxygen-containing intermediates, ensuring the number of active sites. , Under the combined action of the two outcomes mentioned above, Pt/M-PC catalyst has excellent ORR stability. In addition, we also studied the effect of methanol on the catalytic performance during the test.…”
Section: Resultsmentioning
confidence: 99%
“…7,35,46,47 Second, the stronger interaction also increases the local electron density of Pt, thus reducing the location of the d-band center, improving the binding strength of oxygen-containing intermediates, ensuring the number of active sites. 45,48 Under the combined action of the two outcomes mentioned above, Pt/M-PC catalyst has excellent ORR stability. In addition, we also studied the effect of methanol on the catalytic performance during the test.…”
Section: Orr Performance Of Catalystmentioning
confidence: 99%
“…On the one hand, the sluggish kinetics requires high-loading Pt catalysts, which raises the cost of the system. [5][6][7][8] Significant progress has been made in reducing cost and boosting activity through the alloying of platinum with transition metals and the exploration of non-precious metal catalysts. [9][10][11][12][13] On the other hand, a major barrier still exists due to the poor long-term stability of commercial and advanced ORR catalysts in acidic conditions.…”
Section: Introductionmentioning
confidence: 99%